Metabolomic Links between Sugar-Sweetened Beverage Intake and Obesity - Bingjie Zhou; Reiko Ichikawa; Laurence D. Parnell; Sabrina E. Noel; Xiyuan Zhang; Shilpa N. Bhupathiraju; Caren E. Smith; Katherine L. Tucker; Jose M. Ordovas; Chao-Qiang Lai (Journal of Obesity)
Background. Sugar-sweetened beverage (SSB) consumption is highly associated with obesity, but the metabolic mechanism underlying this correlation is not understood. Objective. Our objective was to examine metabolomic links between SSB intake and obesity to understand metabolic mechanisms. Design. We examined the association of plasma metabolomic profiles with SSB intake and obesity risk in 781 participants, aged 45–75 y, in the Boston Puerto Rican Health Study (BPRHS) using generalized linear models, controlling for potential confounding factors. Based on identified metabolites, we conducted pathway enrichment analysis to identify potential metabolic pathways that link SSB intake and obesity risk. Variants in genes encoding enzymes known to function in identified metabolic pathways were examined for their interactions with SSB intake on obesity. Results. SSB intake was correlated with BMI (β = 0.607, P=0.045). Among 526 measured metabolites, 86 showed a significant correlation with SSB intake and 148 with BMI (P≤0.05); 28 were correlated with both SSB intake and BMI (P≤0.05). Pathway enrichment analysis identified the phosphatidylcholine and lysophospholipid pathways as linking SSB intake to obesity, after correction for multiple testing. Furthermore, 8 of 10 genes functioning in these two pathways showed strong interaction with SSB intake on BMI. Our results further identified participants who may exhibit an increased risk of obesity when consuming SSB. Conclusions. We identified two key metabolic pathways that link SSB intake to obesity, revealing the potential of phosphatidylcholine and lysophospholipid to modulate how SSB intake can increase obesity risk. The interaction between genetic variants related to these pathways and SSB intake on obesity further supports the mechanism.